Manuscript of the Mushaf al-Qur’an from the Lingga Kingdom on Penyengat Island, Kepulauan Riau: Analysis of History, Rasm, and Qira'at - Hermawan, Wendy; Putra, Afriadi; Wilaela (Institut Agama Islam Negeri (IAIN) Keiri, 2023)
The Lingga Kingdom is one of the Malay kingdoms that has many historical legacies that are intellectual property. One of them is the large number of al-Qur'an Mushaf manuscripts scattered in this area, especially on Lingga Island and Penyengat Island. This study focused on research on a manuscript found on Penyengat Island with inventory number M. 1 24 and an analysis of the use of rasm and qira`at as the formulation of the problem to be studied. This study was field research used qualitative methods with textological approaches, rasm science, and qira`āt science. Research data obtained from the results of observations, interviews, and documentation obtained during research. The data is reduced and described in detail then drawn a deductive conclusion. Judging from the use of the words hadhf, ziyādah, hamzah, badl, waṣl wa faṣl, and the writing of the qira`āt. This manuscript falls into the category of mushaf with mixed rasm, namely the use of rasm imlā`i and rasm ‘uthmāni simultaneously. Meanwhile, from the aspect of the type of qira`āt used, this manuscript follows the qira`at of Imam Ậṣim al-Kūfi through the narration of Imam Hafṣ.